Unusual Left Atrium and Pulmonary Vein Mass: Correlation of Imaging and Immunohistochemical Stains. (11th September 2019) - Nowroozizadeh, Behdokht; Ibe, Ifegwu; Nowroozizadeh, Sara; Bosemani, Thangavijayan; Sun, Jack; Wang, Beverly
Abstract: Introduction: Intimal sarcoma derived from the pulmonary vein and left atrium is an extremely rare and highly aggressive soft tissue neoplasm. We report a 21-year-old woman with a large filling defect in the pulmonary vein. The lesion extended into the left atrium mimicking a thrombus or a myxoma. Case History: A 21-year-old woman presented with progressively worsening weakness, orthopnea, and exertional dyspnea of 2 weeks' duration. Chest CT scan revealed a large left atrial mass, measuring 8.6 × 4.9 cm, which invaded the right lower lobe of lung and inferior pulmonary vein. Patient underwent right lower lobectomy and surgical resection of the left atrial mass and pulmonary vein. Result: Histologic examination showed a highly cellular, cytologically malignant spindle cell neoplasm in a fascicular pattern. The lesional cells had hyperchromatic tapering nuclei and indistinct cytoplasm. There were numerous mitoses, focal necrosis, and predominantly myxoid stroma. The histologic features suggested the possibility of a myxofibrosarcoma or an intimal sarcoma. The lesional cells were immunoreactive for MDM2 and CDK4, consistent with amplification of the genes on the long arm of chromosome 12. Additionally, the lesional cells were vimentin, CD99, and BCL2 positive while nonimmunoreactive for S100, AE1/3, CD31, CD34, desmin, SMA, MyoD1, myogenin, MPO, and calretinin. Immunohistochemical staining for H3K27me3 was retained. These immunohistochemical findings supported the diagnosis of an intimal sarcoma. Conclusion: Intimal sarcoma commonly involves the aorta and rarely presents as a pulmonary vein or atrial mass. Correlation of imaging and pathologic findings is critical, as intimal sarcoma can mimic a thrombus. Application of immunostains and cytogenetic studies are useful to distinguish intimal sarcoma from other cardiac sarcomas and myxoma of atrium.